A SUBSET OF VENTRAL TEGMENTAL AREA DOPAMINE NEURONS RESPONDS TO ACUTE ETHANOL - MREJERU, A. (Neuroscience, 2015)
The mechanisms by which alcohol drinking promotes addiction in humans and self-administration in rodents remain obscure, but it is well known that alcohol can enhance dopamine (DA) neurotransmission from neurons of the ventral tegmental area (VTA) and increase DA levels within the nucleus accumbens and prefrontal cortex. We recorded from identified DA neuronal cell bodies within ventral midbrain slices prepared from a transgenic mouse line (TH-GFP) using long-term stable extracellular recordings in a variety of locations and carefully mapped the responses to applied ethanol (EtOH). We identified a subset of DA neurons in the medial VTA located within the rostral linear and interfascicular nuclei that fired spontaneously and exhibited a concentration-dependent increase of firing frequency in response to EtOH, with some neurons responsive to as little as 20 mM EtOH. Many of these medial VTA DA neurons were also insensitive to the D2 receptor agonist quinpirole. In contrast, DA neurons in the lateral VTA (located within the parabrachial pigmented and paranigral nuclei) were either unresponsive or responded only to 100 mM EtOH. Typically, these lateral VTA DA cells had very slow firing rates, and all exhibited inhibition by quinpirole via D2 “autoreceptors”. VTA non-DA cells did not show any significant response to low levels of EtOH. These findings are consistent with evidence for heterogeneity among midbrain DA neurons and provide an anatomical and pharmacological distinction between DA neuron sub-populations that will facilitate future mechanistic studies on the actions of EtOH in the VTA.